2013
DOI: 10.1088/0004-637x/772/2/102
|View full text |Cite
|
Sign up to set email alerts
|

Testing Convergence for Global Accretion Disks

Abstract: Global disk simulations provide a powerful tool for investigating accretion and the underlying magnetohydrodynamic turbulence driven by magneto-rotational instability (MRI). Using them to predict accurately quantities such as stress, accretion rate, and surface brightness profile requires that purely numerical effects, arising from both resolution and algorithm, be understood and controlled. We use the flux-conservative Athena code to conduct a series of experiments on disks having a variety of magnetic topolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(173 citation statements)
references
References 41 publications
16
153
3
1
Order By: Relevance
“…As discussed in Section 4.5, the dimensionless numbers, such as α, α m , and B 2 r /B 2 φ , measured in the bound gas are similar to the values reported by Hawley et al (2013) and Jiang et al (2013a). Vertical structures of the disk at each radius, such as the radiation pressure supported optically thick part and strong corona above the photosphere for effective absorption opacity, are also consistent with local shearing box simulations (Jiang et al 2013a(Jiang et al , 2014b.…”
Section: Local Versus Global Modelssupporting
confidence: 82%
“…As discussed in Section 4.5, the dimensionless numbers, such as α, α m , and B 2 r /B 2 φ , measured in the bound gas are similar to the values reported by Hawley et al (2013) and Jiang et al (2013a). Vertical structures of the disk at each radius, such as the radiation pressure supported optically thick part and strong corona above the photosphere for effective absorption opacity, are also consistent with local shearing box simulations (Jiang et al 2013a(Jiang et al , 2014b.…”
Section: Local Versus Global Modelssupporting
confidence: 82%
“…Hawley, Gammie & Balbus 1995;Sorathia et al 2012;Hawley et al 2013) confirmed that MRI can sustain turbulence and dynamo in accretion discs. However, semi-analytical and numerical simulations (see, for example, Masada & Sano 2008;Stone 2011;Hawley et al 2013;Suzuki & Inutsuka 2014;Nauman & Blackman 2015) suggest that the total (Reynolds + Maxwell) stresses due to MRI are insufficient to cause the effective angular momentum transfer in accretion discs in terms of the phenomenological alpha-parameter α S S (Shakura & Sunyaev 1973), giving rather low values α S S ∼ 0.01 − 0.03. Note that from the observational point of view, the alpha-parameter can be reliably evaluated, e.g., from the analysis of non-stationary accretion discs in X-ray novae (Suleimanov, Lipunova & Shakura 2008), dwarf-nova and AM CVn stars (Kotko & Lasota 2012), and turns out to be an order of magnitude higher than typically found in the numerical MRI simulations.…”
Section: Introductionmentioning
confidence: 79%
“…Non-linear numerical simulations (e.g. Hawley, Gammie & Balbus 1995;Sorathia et al 2012;Hawley et al 2013) confirmed that MRI can sustain turbulence and dynamo in accretion discs. However, semi-analytical and numerical simulations (see, for example, Masada & Sano 2008;Stone 2011;Hawley et al 2013;Suzuki & Inutsuka 2014;Nauman & Blackman 2015) suggest that the total (Reynolds + Maxwell) stresses due to MRI are insufficient to cause the effective angular momentum transfer in accretion discs in terms of the phenomenological alpha-parameter α S S (Shakura & Sunyaev 1973), giving rather low values α S S ∼ 0.01 − 0.03.…”
Section: Introductionmentioning
confidence: 96%
“…This is a particularly constraining problem in global simulations. Recently, the convergence and the effect of resolution in global adiabatic (Hawley et al 2013) and locally isothermal (Parkin & Bicknell 2013) simulations were investigated. A convergence study in fully radiative global simulations is difficult to achieve and would go beyond the scope of this paper.…”
Section: Effect Of Resolution Equation Of State and Dust-to-gas Masmentioning
confidence: 99%